PENGARUH PEMBERIAN VARIASI MEDIA PAKAN TERHADAP BERAT SEGAR PER EKOR MAGGOT (Hermetia illucens) - A'yun, Fani Qurrota; Rokhim, S (FKIP Universitas Tanjungpura, 2026)
Black soldier fly larvae (Hermetia illucens) or what are known as maggots are currently the object of much research, both regarding their biological properties and nutritional content. This study aims to determine the effect of variations in feed media on the fresh weight per Hermetia illucens maggot. The type of research is an experiment with a Completely Randomized Design (CRD) design and nine replications per treatment. Three types of feed media used are tofu dregs, corn dregs, and vegetable waste. The results showed that the feed media significantly affected the fresh weight of maggots, with tofu dregs media producing the highest average weight of 1.2 grams per maggot, followed by vegetable waste (0.7 grams), and corn dregs (0.4 grams). These findings indicate that tofu dregs is the most optimal feed media to increase maggot productivity. ANOVA results showed that the type of feed media had a significant effect on the average fresh weight of maggots (p < 0.05).